2020
DOI: 10.30935/cedtech/9274
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions regarding Distance Learning in Higher Education, Smoothing the Transition

Abstract: This paper presents the perceptions on distance learning approaches, assessed through an online survey, using experimental design of ideas (Mind Genomics). Students and professors of higher education institutions who had not yet experienced distance learning before COVID-19 pandemic period participated in the study. The participants belong to the universities located in Mediterranean basin, e.g., Albania, Italy, Morocco, Algeria and few African countries. Results suggest that distance learning will shift many … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 31 publications
2
20
0
1
Order By: Relevance
“…In addition, the concept of teaching strategies is related to study strategies. To obtain constructive study strategies, structure, flexibility, good planning, and good interaction are important, according to several studies [10,12,57,59,60]. Finally, study strategies depend on appropriate and functional technological devices, digital equipment, and digital competence, something that became particularly evident during the pandemic [52,61].…”
Section: Students' Study Strategiesmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the concept of teaching strategies is related to study strategies. To obtain constructive study strategies, structure, flexibility, good planning, and good interaction are important, according to several studies [10,12,57,59,60]. Finally, study strategies depend on appropriate and functional technological devices, digital equipment, and digital competence, something that became particularly evident during the pandemic [52,61].…”
Section: Students' Study Strategiesmentioning
confidence: 99%
“…The quality of teaching occurs in the interface between students and teachers. Particular emphasis has been placed on the importance of interaction and communication between teachers and students [60]. As in other studies, a Swedish survey displayed that many students indicated that the quality of their education was perceived as declining [65].…”
Section: Specific Strategies During the Pandemicmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, select four answers to each question. The answers should illustrate all points of view regarding the questions (Todri et al, 2020). The study deals with the issue of WHO CAN ONE TRUST in 2021, a topic of interest in terms of the problem, the individuals, and the specific actions.…”
Section: Step 1: Define the Problem Select Four Questions That 'Tell A Story'mentioning
confidence: 99%